Development of Learning Media based on Android Games for Children with Attention Deficit Hyperactivity Disorder - Agustini, Maria; Yufiarti, Yufiarti; Wuryani, Wuryani (International Journal of Interactive Mobile Technologies (iJIM), 2020)
This is a learning media with the scope of ADHD (Attention Deficit Hyperactivity Disorder) for children of age 7 – 8 years. The study aims is to education learning media for children with ADHD with existing games. The Dick and Carey instructional model that has been used is a model of development engaging steps of procedural approaches. The achieved results are going to be used to design a teaching and learning media through the Bible Warrior Adventure Games. This research brings out teaching material products that can be accessed by Android application. By using this learning media, the Sunday School Children with ADHD will be able to learn Christian education easily through Android. The results of the field trial found the fact that after testing the use of instructional media was able to facilitate and increase the knowledge and competence of children with special needs ADHD and can create effective learning, and motivate students in learning.